2019
DOI: 10.3168/jds.2018-15859
|View full text |Cite
|
Sign up to set email alerts
|

Housing tiestall dairy cows in deep-bedded pens during an 8-week dry period: Effects on lying time, lying postures, and rising and lying-down behaviors

Abstract: Dairy cow lying behavior is useful in determining the cow's level of welfare, as well as in determining how her environment may affect her comfort and ease of movement. In tiestall systems, cows usually remain in a stall for the duration of their lactation. The dry period offers a unique opportunity to provide alternative housing to the cow with minimal effects on farm housing and management. Our objective was to determine whether housing tiestall cows in deep-bedded pens over an 8-wk dry period altered lying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
(23 reference statements)
3
15
0
Order By: Relevance
“…In our study, the frequency of lame cows was not influenced by the season (P >0.05) (Table 2). These results are concordant with those of Shepley et al (2019b) which assessed the impact of locomotor activity (number of steps) on the lameness score of dairy cows. However, these authors did not indicate any significant differences in the number of lame animals between winter and summer periods in the two types of tie (P = 0.61) and free stall (P = 0.31).…”
Section: Lamenesssupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, the frequency of lame cows was not influenced by the season (P >0.05) (Table 2). These results are concordant with those of Shepley et al (2019b) which assessed the impact of locomotor activity (number of steps) on the lameness score of dairy cows. However, these authors did not indicate any significant differences in the number of lame animals between winter and summer periods in the two types of tie (P = 0.61) and free stall (P = 0.31).…”
Section: Lamenesssupporting
confidence: 88%
“…Unlike traditional confined housing systems, free systems ensure better udder health (De Pinho Manzi et al, 2012;M'Sadak et al, 2015), lower risk of ketosis and better fertility (Relić and Vuković, 2013;Bugueiro et al, 2020), expressing superior potential and performance for improved animal welfare (Vučemilo et al, 2012). In addition, dairy cows housed in free housing benefit from outdoor exercise, positively impacting their health and well-being Popescu et al, 2013;(Dohme-Meier et al, 2014;Shepley et al, 2019b). However, some studies point out that this type of free housing causes a higher risk of lameness (Cook, 2003;Sogstad et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lying behavior was most frequently reported in studies comparing tiestalls to loose housing. All included studies found at least some negative effects of tiestalls on lying patterns, including increased time standing idle and longer standing bouts (Haley et al, 2000), greater frequency of lying interruptions (Jensen, 1999), reduced synchronization of lying behavior (Krohn et al, 1992), more interruptions of the lying down movement (Krohn and Munksgaard, 1993), abnormal lying patterns (Shepley et al, 2019) more collisions lying down (Plesch et al, 2010;Popescu et al, 2014;Shepley et al, 2019), and a greater percentage of cows lying at least partially outside the lying area (Mattiello et al, 2009;Plesch et al, 2010;Ostojić-Andrić et al, 2011). In one study, however, (Müller et al, 1989), the reported benefits of loose housing could not be differentiated from the presence or absence of bedding.…”
Section: Natural Behaviormentioning
confidence: 99%
“…Of the 13 studies in the current review measuring some aspect of lying behavior across different housing types, none found advantages to tethering, and 9 found at least some impairments when cattle were tied compared with loose-housed. These impairments included increases in collisions while lying down, lying outside the lying area, duration to reach recumbency, time spent kneeling, unfulfilled intentions to lie down, abnormal lying postures, and lying interruptions (Krohn et al, 1992;Krohn and Munksgaard, 1993;Plesch et al, 2010;Ostojić-Andrić et al, 2011;Popescu et al, 2014;Shepley et al, 2019).…”
Section: Natural Behaviormentioning
confidence: 99%
“…More recent research echoes these findings, detailing abnormal lying patterns in tiestall systems (e.g., Plesch et al, 2010;Enriquez-Hidalgo et al, 2018;Shepley et al, 2019). Thus, from the cow's perspective (as well as from the public's; Robbins et al, 2019), the expression of certain natural behaviors is hindered.…”
Section: Space To Roammentioning
confidence: 91%